Appropriate admission to rehabilitation: definition of a set of criteria through the Delphi Method. (30th September 2020) - Principi, N; Carnevali, D; Grimoldi, L; Merlo, A; Rodà, F; Auxilia, F; Lombardi, F; Maini, M; Brianti, R; Castaldi, S
Abstract: Background: Controlling inappropriateness of care, a widespread phenomenon, should be a global target in order to improve the quality of care, save money and ensure system sustainability. Inappropriateness is a relevant issue in public health and in rehabilitation medicine specifically. In fact, admitting a patient to a rehabilitation hospital or unit is a complex decision also due to the absence of shared and objective admission criteria. Aim of this study is to define clinical admission criteria and rules in rehabilitation medicine. Methods: A three-round Delphi survey was conducted on a sample of rehabilitation medicine experts skilled in both rehabilitation and healthcare organization. The two initial rounds consisted of an electronic online questionnaire concerning appropriateness of admission to intensive rehabilitation while in the third one a report of the results was provided to the participants. The experts had to score their agreement with each item in the questionnaires, based on either a Likert scale or a dichotomous statement. Consensus between the experts was assessed. Results: A total of 53 health professionals completed the Delphi survey. 19 out of 20 Italian regions were represented. The first round consisted of 8 multiple-choice questions questionnaire. The second round was designed thanks to the suggestions provided by the panelists in the previous one and consisted of a twelve items questionnaire. At the end of the survey, eight criteria of appropriateness of admission to rehabilitation were identified and five rules defining an appropriate admission to a rehabilitation facility were elaborated. Conclusions: This study represents an attempt to create a worthwhile and reliable tool for a more conscious clinical practice in admission to rehabilitation, based on a set of shared criteria and rules. Key messages: Improving appropriateness in healthcare delivery must be a primary goal in public health and in rehabilitation medicine specifically. Delphi method was applied to define shared clinical admission criteria and rules in rehabilitation.